一种分析裂纹对弧齿锥齿轮扭转啮合刚度影响的方法 - 冯刚; 王三民; 李彦彬 (Jixie Chuandong, 2011)
Based on the space meshing theory,the spiral bevel gear tooth surface equation and meshing reference point are established.The influence law of crack position and crack depth on the torsional mesh stiffness of gear is investigated by using the FEM.On this basis,Westinghouse formula is modified to calculate torsional mesh stiffness of gear with penetrating crack.Calculated results show that the effect of crack on the torsional mesh stiffness is strongly marked when the gears mesh in a single pair of teeth.